Equality Value in the Systems of the Democracy of the Tribal People of Baduy - Ulum, Bahrul (Human Rights in the Global South (HRGS), 2022)
This research studies the equality value in the democratic system of the tribal people of Baduy. Amidst increasingly eroded values of traditions, the tribal people of Baduy have adhered to the principle of maintaining their traditions. This research topic departed from the authors’ awareness of the tribal people of Baduy that remain in existence to date, coupled with the fact that tribal law growing amidst the tribal community has served as the root of the history that marks the identity of Indonesia. The process of law enforced in the tribal community is obvious in the process of the appointment of a puun or king. This process begins with superstitious advice (locally known as wangsit) passed by from the earlier puun. This topic is seen as intriguing especially when it is linked with the democratic systems in Indonesia, where these traditional appointment systems also comply with equality value that also exists in the democracy. This research employed empirical juridical methods and an ethnographic approach. The primary data were obtained from direct interviews and the secondary data were from library research. The research population involved all the community members of Baduy and other people living around the tribal community, while the sample involved the tribal head of Baduy, Father Mursid. The data analysis results were narrated and presented in tables before they were analyzed in a descriptive form. The research concludes that the appointment of a puun in the tribal community of Baduy also reflects equality that represents democratic values